Bilirubin induces apoptosis via the mitochondrial pathway in developing rat brain neurons - Rodrigues, CMP (2015)
Increased levels of unconjugated bilirubin, the end-product of heme catabolism, are detrimental to the central nervous system. To examine the role of apoptosis in bilirubin-induced toxicity and to characterize the biochemical pathway of cell death, we exp